2012
DOI: 10.1038/ng.2496
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in GNAL cause primary torsion dystonia

Abstract: Dystonia is a movement disorder characterized by repetitive twisting muscle contractions and postures1,2. Its molecular pathophysiology is poorly understood, in part due to limited knowledge of the genetic basis of the disorder. Only three genes for primary torsion dystonia (PTD), TOR1A (DYT1)3, THAP1 (DYT6)4, and CIZ15 have been identified. Using exome sequencing in two PTD families we identified a novel causative gene, GNAL, with a nonsense p.S293X mutation resulting in premature stop codon in one family and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
262
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(284 citation statements)
references
References 63 publications
12
262
0
10
Order By: Relevance
“…The family initially reported by Bressman et al 29 and the cases reported to date suggest that this dystonia, which was designated DYT25, has a phenotype that is initially predominantly cervical with a tendency to present as craniocervical dystonia with spasmodic dysphonia with or without generalization 28 .…”
Section: Dyt25 Dystoniamentioning
confidence: 99%
See 1 more Smart Citation
“…The family initially reported by Bressman et al 29 and the cases reported to date suggest that this dystonia, which was designated DYT25, has a phenotype that is initially predominantly cervical with a tendency to present as craniocervical dystonia with spasmodic dysphonia with or without generalization 28 .…”
Section: Dyt25 Dystoniamentioning
confidence: 99%
“…Fuchs et al 28 reported twenty-eight patients with dystonia in eight families, including the family initially described by Bressman et al 29 in 1994. They confirmed that mutations in the GNAL gene were the cause of dystonia in these patients.…”
Section: Dyt25 Dystoniamentioning
confidence: 99%
“…Finally, in 2013, two groups reported that mutations in the GNAL gene could cause adult onset primary dystonia (25, 26) with a strong predilection for the cervical region. Cervical dystonia was observed in 93% and spread to other sites in half of cases (25). According to the report of the first group, six of 39 families screened (15%) had mutations in this gene, but the second group found only three patients with mutations among 760 persons screened (26).…”
Section: Genetics and Pathophysiologymentioning
confidence: 99%
“…Five descriptors are utilized to specify the clinical features axis: age at onset, body distribution, temporal pattern, coexistence of other movement disorders, and coexistence of other neurological or systemic manifestations. Age at onset is divided into infancy (0-2 years), childhood (3-12 years), adolescence (13-20 years), early adulthood (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), and late adulthood (>40 years). Body distribution is, as in earlier classifications, divided into focal, segmental, multifocal, generalized, and hemidystonia.…”
Section: Definition and Classificationmentioning
confidence: 99%
“…Yet these genes cause isolated dystonia that is primarily of childhood-onset; isolated dystonia much more commonly begins in adulthood. Against this backdrop, the identification of GNAL mutations (DYT25) is particularly exciting [44], being the first gene linked to adult-onset focal/ segmental dystonia-a condition commonly seen by movement disorders neurologists. Indeed, the discovery of this gene will allow studies exploring potential links between childhood-and adult-onset dystonia-an important question in dystonia research.…”
Section: Dyt25mentioning
confidence: 99%